A catalyst for lignin depolymerization and a preparation method thereof
Patent Information
- Application Number
- CN202611054034.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]温和条件下的非均相催化解聚因具有催化剂易分离、可循环、反应条件可控等优势,成为木质素高效转化的主流技术方向,而高活性、高选择性、高稳定性的非均相催化剂是决定木质素解聚效率与产物分布的核心,其中,贵金属催化剂虽解聚活性优异,但成本高昂、易积碳失活,难以工业化应用,过渡金属催化剂存在活性位点易烧结、选择性差等缺陷
1.本发明制备用于木质素解聚的催化剂,其催化剂载体含有二氧化硅和氧化铝,提供弱酸和弱碱双位点,高效断裂木质素核心C-O-C醚键,为钙钛矿提供氧化还原活性位点,实现木质素深度解聚,利用双功能协同作用,大幅提高木质素解聚率与单环芳香族产物选择性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomass resource utilization technology, specifically a catalyst for lignin depolymerization and its preparation method. Background Technology
[0002] Lignin, a natural polymer, is second only to cellulose in abundance in nature and is widely found in the cell walls of higher plants. Furthermore, lignin is the only polymer in biomass resources containing an aromatic ring structure, thus possessing the potential to serve as a raw material for the production of renewable aromatics.
[0003] Currently, the paper industry produces over 50 million tons of lignin byproducts annually, the vast majority of which are either concentrated and then burned or directly discharged as waste liquid. Regarding concentrated combustion, lignin has a relatively low calorific value, and the large amount of ash it contains causes drawbacks to the combustion process, such as equipment corrosion, low efficiency, and low calorific value. Direct discharge as waste liquid is problematic because of its large molecular weight and low reactivity; lignin is very difficult to degrade in the natural environment, causing serious environmental problems. Therefore, the environmentally friendly and efficient utilization of lignin is urgently needed.
[0004] Lignin, as the most abundant natural aromatic polymer in lignocellulosic biomass, is a huge byproduct of industrial pulping and straw resource utilization. Its molecular structure consists of a three-dimensional network structure formed by cross-linking of phenylpropane units through C-C bonds and CO-C ether bonds. It can be converted into high-value-added chemicals such as monocyclic phenols and aromatic hydrocarbons through catalytic depolymerization. It is the core approach to realize the resource utilization of all components of biomass and replace fossil-based aromatic raw materials.
[0005] Heterogeneous catalytic depolymerization under mild conditions has become the mainstream technology for the efficient conversion of lignin due to its advantages such as easy catalyst separation, recyclability, and controllable reaction conditions. High-activity, high-selectivity, and high-stability heterogeneous catalysts are the core factors that determine the depolymerization efficiency and product distribution of lignin. Among them, noble metal catalysts have excellent depolymerization activity, but they are expensive, prone to carbon deposition and deactivation, and difficult to apply industrially. Transition metal catalysts have defects such as easy sintering of active sites and poor selectivity. Summary of the Invention
[0006] The purpose of this invention is to provide a catalyst for lignin depolymerization and its preparation method. The catalyst support contains silica and alumina, providing dual sites for weak acid and weak base, which efficiently breaks the COC ether bond in the lignin core. Perovskite provides redox active sites, achieving deep depolymerization of lignin. By utilizing the synergistic effect of the dual functions, the depolymerization rate of lignin and the selectivity of monocyclic aromatic products are significantly improved.
[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing a catalyst for lignin depolymerization includes the following steps: Step 1: Using hexadecyltrimethylammonium bromide as a soft template, urea hydrolysis provides a weakly alkaline environment to induce tetraethyl orthosilicate to undergo a sol-gel reaction to generate silica in situ; a surface burr morphology is constructed through a hydrothermal reaction, and then the template is removed by high-temperature calcination to obtain burr-like silica powder with a high specific surface area.
[0008] Step 2: Using alumina hydrosol as a precursor, an alumina gel network is formed by hydrolysis and condensation reaction initiated by ammonium persulfate and controlled by ammonia. Bursted silica is uniformly doped into the network to construct a three-dimensional composite porous structure of silica-alumina. The porous framework is preserved by liquid nitrogen freeze-drying, and finally a catalyst support with high specific surface area and interconnected pores is obtained.
[0009] Step 3: Using a co-precipitation method, sodium carbonate is used as a precipitant to convert lanthanum, strontium, and nickel metal ions into hydroxide precursors, which are uniformly deposited on the surface of the catalyst support. After drying, the precursors are calcined at high temperature to obtain a catalyst for lignin depolymerization.
[0010] Furthermore, the specific preparation steps for the burr-like silica powder are as follows: Hexadecyltrimethylammonium bromide, urea, silica particles, and deionized water were added to a reaction vessel and stirred for 40-50 minutes at 20-25°C and 500-600 rpm. Then, isopropanol and tetraethyl orthosilicate were added, and stirring was continued for another 40-50 minutes. The mixture was then heated to 80-90°C and reacted for 18-20 hours. After filtration, the filter cake was washed 2-4 times with deionized water and dried under vacuum at 60-70°C for 1-2 hours. The cake was then transferred to a muffle furnace and calcined at 550-580°C for 6-7 hours to obtain burr-like silica powder.
[0011] Furthermore, the ratio of hexadecyltrimethylammonium bromide, urea, silica particles, deionized water, isopropanol, and tetraethyl orthosilicate is 22-24g: 20-22g: 10-12g: 500-600mL: 20-30mL: 8-10mL.
[0012] Furthermore, the specific preparation steps of the catalyst support are as follows: Alumina hydrosol and ethanol were added to a reaction vessel and stirred for 20-30 min at 20-25℃ and 400-500 r / min. Then, ammonium persulfate initiator was added and stirring was continued for 40-50 min. Next, 5-6% ammonia solution and burr-like silica powder were added and heated to 80-90℃ to promote gel condensation. Stirring was continued for 48-50 h, and the mixture was allowed to cool naturally to room temperature. It was then freeze-dried in liquid nitrogen for 12-14 h to obtain the catalyst support.
[0013] Furthermore, the ratio of alumina hydrosol, ethanol, ammonium persulfate, ammonia solution and burr-like silica powder is 100-110g: 800-900mL: 1-2g: 20-30mL: 12-14g.
[0014] Furthermore, the specific preparation steps for the catalyst used for lignin depolymerization are as follows: Lanthanum nitrate, strontium nitrate, nickel nitrate, catalyst support, and deionized water were added to a reactor and stirred for 20-30 minutes at 20-25℃ and 400-500 r / min. Then, 0.8-0.9 mol / L sodium carbonate solution was added as a precipitant, and the mixture was heated to 80-90℃. The pH of the solution was adjusted to 8-8.5, and the mixture was allowed to stand overnight for precipitation. The mixture was then filtered, and the resulting sample was dried in a drying oven at 110-120℃ for 12-14 hours. The sample was then transferred to a muffle furnace and calcined at 800-900℃ for 5-7 hours to obtain a catalyst for lignin depolymerization.
[0015] Furthermore, the ratio of lanthanum nitrate, strontium nitrate, nickel nitrate, catalyst support, and deionized water is 1.3-1.4g: 0.57-0.59g: 1.16-1.18g: 5-8g: 100-110mL.
[0016] The beneficial effects of this invention are: 1. The present invention prepares a catalyst for lignin depolymerization. The catalyst support contains silica and alumina, providing dual sites of weak acid and weak base, efficiently breaking the COC ether bond in the core of lignin, providing redox active sites for perovskite, realizing deep depolymerization of lignin, and utilizing the synergistic effect of the dual function to significantly improve the depolymerization rate of lignin and the selectivity of monocyclic aromatic products.
[0017] 2. The catalyst for lignin depolymerization prepared in this invention is prepared by using a soft template method to prepare burr-like silica, which is then combined with alumina aerogel to form a three-dimensional interconnected hierarchical porous support. The specific surface area is much higher than that of pure perovskite and single oxide supports, providing sufficient diffusion channels for lignin macromolecules and significantly improving the contact efficiency between reactants and active sites. The La-Sr-Ni active components are uniformly loaded onto the surface of the composite aerogel support by co-precipitation. During high-temperature calcination, the support plays a confinement role, effectively inhibiting the agglomeration and growth of perovskite grains, greatly increasing the exposure of active sites, and significantly improving the catalytic activity compared with traditional bulk pure perovskite catalysts.
[0018] 3. The catalyst for lignin depolymerization of the present invention contains an aerogel composite framework, which can withstand high temperatures and is not easily collapsed. At the same time, the porous structure of the support can accommodate a small amount of by-product coke, which alleviates the problem of active sites being covered and solves the problems of easy carbon accumulation and insufficient recyclability of traditional pure perovskite catalysts. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1: A method for preparing a catalyst for lignin depolymerization, comprising the following steps: S1: Add 22g hexadecyltrimethylammonium bromide, 20g urea, 10g silica granules and 500mL deionized water to a reaction vessel, stir for 40min at 20℃ and 500r / min, then add 20mL isopropanol and 8mL tetraethyl orthosilicate, continue stirring for 40min, heat to 80℃, continue the reaction for 18h, filter, wash the filter cake twice with deionized water, vacuum dry at 60℃ for 1h, transfer to a muffle furnace, heat to 550℃ and calcine for 6h to obtain burr-like silica powder.
[0021] S2: Add 100g of alumina hydrosol and 800mL of ethanol to the reactor and stir for 20min at 20℃ and 400r / min. Then add 1g of initiator ammonium persulfate and continue stirring for 40min. Then add 20mL of 5% ammonia solution and 12g of burr-like silica powder, heat to 80℃ to promote gel condensation, continue stirring for 48h, cool naturally to room temperature, and freeze-dry with liquid nitrogen for 12h to obtain the catalyst support.
[0022] S3: 1.3g lanthanum nitrate, 0.57g strontium nitrate, 1.16g nickel nitrate, 5g catalyst support, and 100mL deionized water were added to a reactor and stirred for 20min at 20℃ and 400r / min. Then, 0.8mol / L sodium carbonate solution was added as a precipitant, heated to 80℃, and the pH of the solution was adjusted to 8. After standing and settling overnight, the mixture was filtered and vacuum filtered. The obtained sample was dried in a drying oven at 110℃ for 12h, transferred to a muffle furnace, and calcined at 800℃ for 5h to obtain a catalyst for lignin depolymerization.
[0023] Example 2: A method for preparing a catalyst for lignin depolymerization, comprising the following steps: S1: Add 23g hexadecyltrimethylammonium bromide, 21g urea, 11g silica granules and 550mL deionized water to a reaction vessel, stir for 45min at 22.5℃ and 550r / min, then add 25mL isopropanol and 9mL tetraethyl orthosilicate, continue stirring for 45min, heat to 85℃, continue the reaction for 19h, filter, wash the filter cake 3 times with deionized water, vacuum dry at 65℃ for 1.5h, transfer to a muffle furnace, heat to 565℃ and calcine for 6.5h to obtain burr-like silica powder.
[0024] S2: Add 105g of alumina hydrosol and 850mL of ethanol to the reactor and stir for 25min at 22.5℃ and 450r / min. Then add 1.5g of initiator ammonium persulfate and continue stirring for 45min. Then add 25mL of 5.5% ammonia solution and 13g of burr-like silica powder, heat to 85℃ to promote gel condensation, continue stirring for 49h, cool naturally to room temperature, and freeze-dry with liquid nitrogen for 13h to obtain the catalyst support.
[0025] S3: 1.35g lanthanum nitrate, 0.58g strontium nitrate, 1.17g nickel nitrate, 6.5g catalyst support, and 105mL deionized water were added to a reactor and stirred for 25min at 22.5℃ and 450r / min. Then, 0.85mol / L sodium carbonate solution was added as a precipitant, heated to 85℃, and the pH of the solution was adjusted to 8.25. After standing overnight for precipitation, the mixture was filtered and vacuum filtered. The obtained sample was dried in a drying oven at 115℃ for 13h, transferred to a muffle furnace, and calcined at 850℃ for 6h to obtain a catalyst for lignin depolymerization.
[0026] Example 3: A method for preparing a catalyst for lignin depolymerization, comprising the following steps: S1: Add 24g hexadecyltrimethylammonium bromide, 22g urea, 12g silica granules and 600mL deionized water to a reaction vessel, stir for 50min at 25℃ and 600r / min, then add 30mL isopropanol and 10mL tetraethyl orthosilicate, continue stirring for 50min, heat to 90℃, continue the reaction for 20h, filter, wash the filter cake 4 times with deionized water, dry under vacuum at 70℃ for 2h, transfer to a muffle furnace, heat to 580℃ and calcine for 7h to obtain burr-like silica powder.
[0027] S2: Add 110g of alumina hydrosol and 900mL of ethanol to a reactor and stir for 30min at 25℃ and 500r / min. Then add 2g of initiator ammonium persulfate and continue stirring for 50min. Then add 30mL of 6% ammonia solution and 14g of burr-like silica powder, heat to 90℃ to promote gel condensation, continue stirring for 50h, cool naturally to room temperature, and freeze-dry with liquid nitrogen for 14h to obtain the catalyst support.
[0028] S3: 1.4g lanthanum nitrate, 0.59g strontium nitrate, 1.18g nickel nitrate, 8g catalyst support, and 110mL deionized water were added to a reactor and stirred for 30min at 25℃ and 500r / min. Then, 0.9mol / L sodium carbonate solution was added as a precipitant, heated to 90℃, and the pH of the solution was adjusted to 8.5. After standing and settling overnight, the mixture was filtered and vacuum filtered. The filtered sample was dried in a drying oven at 120℃ for 14h, transferred to a muffle furnace, and calcined at 900℃ for 7h to obtain a catalyst for lignin depolymerization.
[0029] Comparative Example 1: Based on Example 3, the burr-like silica powder in step S2 was replaced with silica particles in step S1.
[0030] Comparative Example 2: Based on Example 3, the catalyst support in step S3 was replaced with the burr-like silica powder prepared in step S1.
[0031] Comparative Example 3: Based on Example 3, the catalyst support in step S3 was removed.
[0032] The specific steps of lignin depolymerization in the examples and comparative examples are as follows: Add 0.6-0.8g of sodium lignin sulfonate and 0.3-0.5g of perovskite catalyst to the reactor, then add propanol, ethanol, and methanol. Heat to 180-200℃ and continue stirring for 6-10 hours. After the reaction is complete, cool the reactor to room temperature. The reaction products are separated into gas, liquid, and solid. After the depolymerization reaction in the reactor is complete, transfer the generated reaction liquid to a beaker. Then, clean the reactor with anhydrous ethanol and pour the cleaning solution into the same beaker. Collect the reaction liquid and centrifuge it at 1000-1100 r / min for 5-7 min to precipitate the solid impurities. After centrifugation, use filtration to separate the solid and liquid. Remove the alcohol solvent from the obtained liquid product using a rotary evaporator to obtain bio-oil, thus completing the depolymerization of lignin.
[0033] Performance tests were conducted on Examples 1-3 and Comparative Examples 1-3, and the results are shown in Table 1: Table 1
[0034] As shown in Table 1, in Comparative Example 1, the use of raw silica particles instead of burr-like silica resulted in the loss of the unique burr-like morphology and hierarchical porous structure. Consequently, the specific surface area of the support was significantly reduced, resulting in insufficient diffusion and mass transfer channels for lignin macromolecules and a significant decrease in the contact efficiency between reactants and catalytic active sites. After the composite of ordinary silica and alumina hydrosol, a three-dimensional interconnected porous framework could not be formed, weakening the confinement effect of the support on the perovskite components and making the active components prone to slight agglomeration. The pore volume and channel structure of the support deteriorated, reducing its capacity to accommodate the reaction byproduct coke and decreasing its resistance to carbon deposition.
[0035] In Comparative Example 2, only burr-like silica was used as the support, excluding the alumina aerogel component. The support only had a single acidic site in silica and lacked the weak base sites provided by alumina, making it impossible to construct a weak acid-weak base bifunctional catalytic system. This significantly reduced the efficiency of breaking the ether bonds of lignin COC, and the bifunctional synergistic catalytic effect failed. Without the support of the three-dimensional framework of alumina aerogel, the high-temperature structural stability of the support decreased, and long-term reactions were prone to pore collapse. The lack of acid and base sites on the support led to incomplete depolymerization of lignin, increased side reactions, reduced selectivity of monocyclic aromatic products, weakened resistance to carbon deposition, and accelerated activity decay during recycling.
[0036] In Comparative Example 3, the catalyst support was completely abandoned, and a pure-phase lanthanum-strontium-nickel perovskite catalyst was used. Without the confinement and dispersion of a porous support, the perovskite grains severely agglomerated and sintered during high-temperature calcination, resulting in the near loss of specific surface area and pore structure, and extremely low exposure of active sites. Without the acid-base dual sites provided by silica-alumina, the catalyst relied solely on the redox sites of perovskite, which could not efficiently break lignin ether bonds, leading to a significant decrease in depolymerization rate and product selectivity. Without a porous support to accommodate coke, the catalytic sites were easily covered by byproducts, resulting in extremely poor resistance to carbon deposition. The catalyst rapidly deactivated during recycling, and the activity retention rate was significantly reduced, making it completely unable to meet the requirements for efficient and stable depolymerization of lignin.
[0037] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a catalyst for lignin depolymerization, characterized in that, Includes the following steps: Step 1: Using hexadecyltrimethylammonium bromide as a soft template, urea hydrolysis provides a weakly alkaline environment to induce tetraethyl orthosilicate to undergo a sol-gel reaction to generate silica in situ; a surface burr morphology is constructed through a hydrothermal reaction, and then the template is removed by high-temperature calcination to obtain burr-like silica powder with high specific surface area. Step 2: Using alumina hydrosol as a precursor, an alumina gel network is formed by hydrolysis and condensation reaction initiated by ammonium persulfate and controlled by ammonia. Bursted silica is uniformly doped into the network to construct a three-dimensional composite porous structure of silica-alumina. The porous framework is preserved by liquid nitrogen freeze-drying, and finally a catalyst support with high specific surface area and interconnected pores is obtained. Step 3: Using a co-precipitation method, sodium carbonate is used as a precipitant to convert lanthanum, strontium, and nickel metal ions into hydroxide precursors, which are uniformly deposited on the surface of the catalyst support. After drying, the precursors are calcined at high temperature to obtain a catalyst for lignin depolymerization.
2. The method for preparing a catalyst for lignin depolymerization according to claim 1, characterized in that, The specific preparation steps for the burr-like silica powder are as follows: Hexadecyltrimethylammonium bromide, urea, silica particles, and deionized water were added to a reaction vessel and stirred for 40-50 minutes at 20-25°C and 500-600 rpm. Then, isopropanol and tetraethyl orthosilicate were added, and stirring was continued for another 40-50 minutes. The mixture was then heated to 80-90°C and reacted for 18-20 hours. After filtration, the filter cake was washed 2-4 times with deionized water and dried under vacuum at 60-70°C for 1-2 hours. The cake was then transferred to a muffle furnace and calcined at 550-580°C for 6-7 hours to obtain burr-like silica powder.
3. The method for preparing a catalyst for lignin depolymerization according to claim 2, characterized in that, The ratio of hexadecyltrimethylammonium bromide, urea, silica particles, deionized water, isopropanol and tetraethyl orthosilicate is 22-24g: 20-22g: 10-12g: 500-600mL: 20-30mL: 8-10mL.
4. The method for preparing a catalyst for lignin depolymerization according to claim 1, characterized in that, The specific preparation steps of the catalyst support are as follows: Alumina hydrosol and ethanol were added to a reaction vessel and stirred for 20-30 min at 20-25℃ and 400-500 r / min. Then, ammonium persulfate initiator was added and stirring was continued for 40-50 min. Next, 5-6% ammonia solution and burr-like silica powder were added and heated to 80-90℃ to promote gel condensation. Stirring was continued for 48-50 h, and the mixture was allowed to cool naturally to room temperature. It was then freeze-dried in liquid nitrogen for 12-14 h to obtain the catalyst support.
5. A method for preparing a catalyst for lignin depolymerization according to claim 4, characterized in that, The ratio of the alumina hydrosol, ethanol, ammonium persulfate, ammonia solution and burr-like silica powder is 100-110g: 800-900mL: 1-2g: 20-30mL: 12-14g.
6. The method for preparing a catalyst for lignin depolymerization according to claim 1, characterized in that, The specific preparation steps of the catalyst for lignin depolymerization are as follows: Lanthanum nitrate, strontium nitrate, nickel nitrate, catalyst support, and deionized water were added to a reactor and stirred for 20-30 minutes at 20-25℃ and 400-500 r / min. Then, 0.8-0.9 mol / L sodium carbonate solution was added as a precipitant, and the mixture was heated to 80-90℃. The pH of the solution was adjusted to 8-8.5, and the mixture was allowed to stand overnight for precipitation. The mixture was then filtered, and the resulting sample was dried in a drying oven at 110-120℃ for 12-14 hours. The sample was then transferred to a muffle furnace and calcined at 800-900℃ for 5-7 hours to obtain a catalyst for lignin depolymerization.
7. A method for preparing a catalyst for lignin depolymerization according to claim 6, characterized in that, The ratio of lanthanum nitrate, strontium nitrate, nickel nitrate, catalyst support, and deionized water is 1.3-1.4g: 0.57-0.59g: 1.16-1.18g: 5-8g: 100-110mL.
8. A catalyst for lignin depolymerization, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.